A narrative review of retinal vascular parameters and the applications (Part II): Diagnosis in stroke - Yuan Gao; Lijun Xu; Ning He; Yuchuan Ding; Wenbo Zhao; Tingting Meng; Ming Li; Jiaqi Wu; Yazeed Haddad; Xuxiang Zhang; Xunming Ji (Brain Circulation, 2023)
The retina, as an external extension of the diencephalon, can be directly, noninvasively observed by ocular fundus photography. Therefore, it offers a convenient and feasible mode to study nervous system diseases. Caliber, tortuosity, and fractal dimension, as three commonly used retinal vascular parameters, are not only the reflection of structural changes in the retinal microcirculation but also capture the branching pattern or density changes of the retinal microvascular network. Therefore, it contributes to better reflecting the subclinical pathological changes (e.g., lacunar stroke and small cerebral vascular disease) and predicting the risk of incident stroke and recurrent stroke.